Examining the moderation and mediation effects of mental toughness on perceived stress and anxiety amongst athletes and non-athletes - Loh, Benjamin Jun Ming (Nanyang Technological University, 2020)
Stress causes health-related issues such as anxiety, which undermines performance in various achievement contexts (students and athletes). The association between perceived stress and anxiety is well-recognized, while mental toughness (MT) is known to benefit outcomes by lowering both perceived stress and anxiety. However, the role of MT in explaining the stress-anxiety relationship was not well-established. The study purpose was to test whether MT moderates and mediates the relationship between perceived stress and anxiety, and whether such effects are stronger in athletes than non-athletes. 320 students (Mage = 23.2 years, SD = 2.1; 160 athletes, 160 non-athletes; 165 males, 155 females) from Nanyang Technological University completed self-reported questionnaires. The study variables perceived stress, anxiety and MT were measured using the Perceived Stress Scale (PSS), State-Trait Anxiety Inventory – Trait Scale (STAI-T) and Mental Toughness Questionnaire 10 Items (MTQ-10). Multiple hierarchical analyses revealed that MT moderated the relationship only in non-athletes, and partially mediated the relationship in both athletes and non-athletes. Moreover, mediation was stronger in athletes; MT accounted for a significantly greater variance in anxiety outcome in athletes (82%) than non-athletes (33%), highlighting the importance of MT as a stress buffer pathway to lower anxiety. Additional variable control analyses revealed that training years did not substantially benefit MT effects, suggesting that practice quality and competition level might be more critical in MT development. This study presents novel findings on the moderation and mediation perspective of MT on the stress-anxiety relationship, which provides a more comprehensive foundation for future MT interventions using sports.